Analisis Pengaruh Kecerdasan Emosional Dan Kecerdasan Spiritual Terhadap Kinerja Auditor Pada Perusahaan Industri Di Bandar Lampung. (Study Kasus pada Perusahaan Industri di Bandar Lampung) - Nuria Erisna; Ines Genevine; Riswan RISWAN (Jurnal Akuntansi dan Keuangan, 2012)
The purpose of this study is to determine how much influence emotional intelligence(EQ) and spiritual intelligence (SQ) on the performance of the auditor either partially or simultaneously on industrial companies in Sydney which is the object of this research. And of the two independent variables will also be sought where the dominant variable affecting the performance of auditors. This study uses a causal research design that studies the relationship between the number of variables in which the independent variables in the study is emotional intelligence (X1) and spiritual intelligence (X2), the dependent variable is the performance of the auditor (Y). Source of data used are primary data with a questionnaire method of data collection, amounting to 30 items, which are distributed to 25 respondents (auditor).Â  The results show that emotional intelligence and spiritual intelligence significant positive effect on the performance of auditors in industrial enterprises in Bandar Lampung. The better the emotional and spiritual intelligence, the better the performance of the auditor. Emotional and spiritual intelligence contributes to the performance of the auditor is 73.9% while the remaining 26.1% is determined by other factors.